Diagnostic and therapeutic recommendations on Helicobacter pylori infection. Recommendations of the Working Group of the Polish Society of Gastroenterology - Krzysztof Jaroń; Anna Pietrzak; Jarosław Daniluk; Krystian Adrych; Anita Gąsiorowska; Barbara Skrzydło-Radomańska; Ewa Małecka-Wojciesko; Małgorzata Zwolińska-Wcisło; Marek Waluga; Jarosław Reguła; Grażyna Rydzewska (Gastroenterology Review)
Helicobacter pylori remains a major health problem worldwide, causing considerable morbidity and mortality due to peptic ulcer disease and gastric cancer. These guidelines constitute an update of the previous "Recommendations on the diagnosis and management of Helicobacter pylori infection” issued in 2014. They have been developed by a Task Force organized by the Governing Board of the Polish Society of Gastroenterology. They discuss, with particular emphasis on new scientific data covering papers published since 2014: the epidemiology, clinical presentation, diagnostic principles and criteria for the diagnosis, and recommendations for the treatment of H. pylori infection. The guidelines in particular determine which patients need to be tested and treated for infection. The Task Force also discussed recommended treatment algorithms. Accordingly, a combination of available evidence and consensus-based expert opinion were used to develop these best practice advice statements. It is worth noting that guidelines are not mandatory to implement but they offer advice for pragmatic, relevant and achievable diagnostic and treatment pathways based on established key treatment principles and using local knowledge and available resources to guide regional practice.